PENGARUH PENGGUNAAN E-BOOK DALAM PEMBELAJARAN BAHASA ARAB DI SEKOLAH DASAR - Kodratullah; Lili Musyafaah (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
The study aims to evaluate the impact of the use of e-books on learning Arabic in primary schools. The research method used was quantitative with experimental design involving 60 students of 4th and 5th grade at two primary schools in Jakarta. Students were divided into two groups: the experimental group using e-books and the control group using printed books. The results of the study showed that students using ebooks had a significant improvement in their Arabic-language skills test scores compared to students using a printed book. The average increase in scores in experimental groups was 20%, while in the control groups only 10%. Furthermore, the questionnaires given to students indicated that 85% of them felt more motivated and interested in learning Arabic with ebooks. The findings indicate that e-books can be an effective tool in improving Arabic learning in primary schools. However, e-book implementation also requires adequate technology infrastructure support as well as training for teachers to be able to integrate this technology optimally.